N.M. Tussupova, Sh.Sh. Mulkibayeva, G.K. Esimova, R.S. Omarova Case-stimulated learning withinHistology class activities (integrated teaching in medical school) (Journal of Educational Sciences, 2016)
The article discusses the Case–studу, teaching method based on specific clinical cases, providing the relationship between the basic disciplines as histology, and clinical disciplines. Histology fundamental part of many biomedical disciplines, the link between macroscopic and microscopicmeasurements, the bridge between the anatomy and the more subtle, ephemeral worlds of biochemistry, physiology and pharmacology.For a long time in teaching histology was used established methods, which remained practically unchanged. Classical methods of study of histological preparations involve the use of light microscopy. The development and use of modern information technologies in education significantly affected the quality of the studies on the histology, made them more visible, enhancing the perception of educational material for students. Case-studу at the Department of histology at the Kazakh national medical University, we began to be used in a modular system of training in the discipline «Histology-2 2012 for the 3rd year students on specialty «General medicine». Training method «case-study» asked the teachers of the Department in the first place, considerable preparatory work. Accordingly modules were developed clinical cases, taking into account the continuity of prerequisites and post requisites. We emphasize the fundamental importance of the preliminary theoretical and practical training ofstudents before consideration of the case. Students noted the fundamental difference between the cases before mechanical memorization. According to students, these courses helped to realize the practical importanceof knowledge in a very «virtual» and therefore obscure the subject as histology, became a strong motivation for a more meaningful study of the microscopic features of the structures.
Keywords: teaching methods; teaching histology; case studies; innovative teaching methods; active learning methods